Perfil sociodemográfico e de saúde de menores de cinco anos e mulheres em idade reprodutiva de aldeias indígenas Pataxó, Minas Gerais, Brasil - Santos, Anabele Pires [UNIFESP] (2018)
Objective: To describe sociodemographic and health profile of children under five years old and women aged 14 to 49 years old from indigenous villages Pataxó, Minas Gerais, Brazil. Methodology: Cross-sectional population-based epidemiological study conducted in 2011 with Pataxó, Minas Gerais. It was used a structured questionnaire based on the I National Survey of Health and Nutrition of Indigenous (Abrasco/Göteborg University/Funasa) to evaluate sociodemographic and health profile. Anthropometric measurements (weight and height for women and children) and waist circumference (for women) was performed according to the World Health Organization (WHO) protocols. The classification of nutritional status was based on cut-off points established by WHO. Frequencies of categorical variables and mean or median of continuous variables were calculated. Student´s t test was used to identify differences between means, while proportions were compared by Pearson Chi-square test, adopting P <0.05. Multiple logistic regression model was used to identify sociodemographic factors associated with overweight among indigenous women. Data were analyzed using PASW software, version 17.0, adopting P <0.05. Results:It were evaluated 34 children (<5 years) and 69 women (14-49 years) living in 5 villages of Pataxó located in Araçuaí, Açucena, Guanhães and Carmésia. Among children under five years, most of the children were born in the hospital, all had prenatal care and 82.4% had six or more appointments. Universal coverage was found for most of the vaccines evaluated. Prevalence of hospitalization in the last 12 months was 23.5%, but no hospitalization was due to respiratory infections and only 1 child was hospitalized with diarrhea. Occurrence of diarrhea in the last week was reported for 17.6% of the children and cough for 35.3%. About half of children had taken high dosages of vitamin A in the last six months. Only 8.8% of children had a growth monitoring record in the last month prior to the survey. Among children under two years, 100% started breastfeeding and median duration of breastfeeding was 12 months. Among women, 26.1% were adolescents (age> 14 to <20 years), 40.6% had completed primary school and most were married. It was verified that 13% used medication for blood pressure, 5.8% for diabetes mellitus and anemia. Regarding the number of hospital admissions, 67.5% of the women had a hospital stay and 32.5% had two or more admissions. Most had already become pregnant with the first gestation in adolescence and most of them became pregnant 2 to 4 times. Family income of the majority of women came from the sale of handicrafts or other production and approximately half received Bolsa Família social benefit. The majority of food was obtained from nearby markets, basic food basket and cultivation or home / collective breeding. Age, village of origin and age of first pregnancy were independently associated with overweight among non-pregnant women. Conclusions: The findings suggest improvements in primary care actions such as prenatal care, child care, immunization, implementation of micronutrient supplementation programs, infant growth and development, breastfeeding, reduction and prevention of risk factors for overweight in indigenous women and nutritional status of the population described. The study intends to subsidize discussions about indigenous health programs, especially in actions aimed at improving the nutritional status of indigenous children and women and living conditions of Brazilian natives.